Molecular mechanism of antihistamines recognition and regulation of the histamine H1 receptor - Dandan Wang; Qiong Guo; Zhangsong Wu; Ming Li; Binbin He; Yang Du; Kaiming Zhang; Yuyong Tao (2024)
Abstract Histamine receptors are a group of G protein-coupled receptors (GPCRs) that play important roles in various physiological and pathophysiological conditions. Antihistamines that target the histamine H 1 receptor (H 1 R) have been widely used to relieve the symptoms of allergy and inflammation. Here, to uncover the details of the regulation of H 1 R by the known second-generation antihistamines, thereby providing clues for the rational design of newer antihistamines, we determine the cryo-EM structure of H 1 R in the apo form and bound to different antihistamines. In addition to the deep hydrophobic cavity, we identify a secondary ligand-binding site in H 1 R, which potentially may support the introduction of new derivative groups to generate newer antihistamines. Furthermore, these structures show that antihistamines exert inverse regulation by utilizing a shared phenyl group that inserts into the deep cavity and block the movement of the toggle switch residue W428 6.48 . Together, these results enrich our understanding of GPCR modulation and facilitate the structure-based design of novel antihistamines.